Manufacture of titanium alloys by powder metallurgy for biomedical implants - Goi, Lim Sheng (2008)
This project aims in the study of the application of powder metallurgy for the production of biomaterial implants (e.g. Ti6A14V and Ti-Si-Zr) with engineered porosity and mechanical properties (i.e. lower yield strength).